Hambatan dalam Menerapkan Peran Case Manager di Indonesia: Literature Review - Ahmad Safar Najamuddin (Jurnal Medika Hutama, 2022)
Background: Case managers are the driving force for case management in hospitals, which serve to fulfill patient needs and achieve cost-effectiveness of services in order to achieve good service. However, since the case manager was first introduced by KARS in the 2012 version of the hospital accreditation standard, until now this profession is still not optimal in carrying out its roles and functions. Purpose: Knowing the barriers to implementing the role of case manager in Indonesian hospitals in the last decade. Methods: This research was conducted using a literature review technique, through Google Scholar, ScienceDirect, and EBSCOhost; with a range of 2012 to 2021, and produced 9 articles that meet the criteria and will be used in the discussion. Results: The author finds that in general there are at least three obstacles in implementing the role of the case manager in Indonesia, including organizational barriers, activity barriers, and evaluation barriers. The most common problem is that the case manager does not have a clear definition of the main tasks of the function. Screening and assessment activities are often hampered because there is no clear format for initial patient screening. All hospitals have not set indicators to evaluate the results of case manager services. Conclusion: Organizing barriers are the main obstacles in the role of case managers, so it requires the development and clear professional standards of case managers.